Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

Characteristics and mechanism of karst groundwater cycle evolution under large-scale exploitation: a case study of the Yanxi karst groundwater system - Yawei Feng; Fengxin Kang; Fengfeng Shi; Xuesen Wang; Xianzhou Meng; Yifu Fu; Aijun Li; Hao Chen; Qingcheng He (Carbonates and Evaporites, 2026)

Limosilactobacillus reuteri Y15 enhances uterine development and function in gilts via the gut-uterus axis - Juanli Huo; Shen Li; Dongxin Lu; Lei Li; Weidong Zhang; Yukang Li; Bin Yao; Yong Zhao; Yawei Zhang; Jie Zhang; Huiying Luo (Theriogenology, 2026)

Isolation and identification of tropical source Lactobacillus plantarum CK3 and its effects on fatty liver in laying hens - Yongzhen Chen; Xinyu Feng; Xinyi Zhang; Andrea Abreo Medina; Jiayu Feng; Xin Li; Meiyu Duan; Yawei Qiu; Fang Gan (Research in Veterinary Science, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Enhancing the flotation separation of lithium adsorbents via sodium oleate-induced hydrophobic modification: Hydrophobization mechanism and field validation - Yuanliang Yang; Gang Jin; Jianqiang Tao; Chang Liu; Yawei Han; Ruoyu Ding; Yaqi Yang; Xiaolong Xiao; Xiaobing Li (Journal of Water Process Engineering, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Structural changes of costameres and actomyosin induced by postmortem resonant stimulation - Wanhong He; Yingbo Peng; Haixia Huang; Hao Wen; Chuanfeng Liu; Zhenzhen Li; Yawei Zhang (Food Research International, 2026)

Robust water matrix tolerance for selective photocatalytic detoxification and decarboxylation of D-Glu and D-MeAsp in microcystin-LR via nanoconfinement-mediated active site regulation - Chengzhuo Yu; Jin Xu; Silong Wang; Li Xiong; Fanglan Geng; Yarui Wang; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2026)

Anti-melanogenic bioactive peptides: Molecular mechanisms, source, preparation, structural optimization and cross-field prospective application - Qun Yu; Haozhe Li; Yanxia Sun; Yawei Yu (Trends in Food Science & Technology, 2026)

Seasonal shifts in dissolved organic matter composition drive the formation of nitrogenous disinfection byproducts via a carbon-nitrogen coupling mechanism in source water - Tianyu Chen; Shiyang Yu; Qiurui Zhang; Jing Qian; Yonghong Bi; Anen He; Lingxiangyu Li; Nanwen Zhu; Jitao Lv; Zhigang Li; Yawei Wang; Guibin Jiang (Environmental Research, 2026)

Urban–rural divergence of wintertime organic aerosol molecular fingerprints in PM2.5 revealed by FT–ICR MS - Shanshan Tang; Jintian Zhang; Yuansheng Wang; Jitao Lv; Lei Liu; Weijun Li; Yawei Wang (Atmospheric Environment, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Consistency and specificity of soil and microbial responses among crops to mulching practices in semi-arid rainfed agroecosystems in China - Yao Zhang; Yuwei Chai; Xichen Wang; Hongbo Cheng; Yawei Li; Jiantao Ma; Lei Chang; Shouxi Chai (European Journal of Agronomy, 2026)

Dual-nitrogen coordination engineering enables porous carbon-confined Pt-FeN4 atomic interfaces for durable, low-Pt PEM fuel cells - Xiaoqian Xu; Nengneng Xu; Qin Cao; Yuheng Guo; Meng Li; Yuhao Liu; Yawei Li; Guicheng Liu; Woochul Yang; Jong Min Kim; Momo Safari; Jinli Qiao (Chemical Engineering Journal, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Cross-scale mechanisms and molecular–ecological thresholds of phthalate stress in the cucumber–soil system - Zhe Li; Lei Wang; DongDong Tuo; FuXin Huang; YaWei Shi; Ying Zhang (Journal of Hazardous Materials, 2026)

A computational screening study of Dual-Metal M1M2@1T-MoS2 with various coordination environments as catalysts for the hydrogen evolution reaction - Tingting Li; Guohao Yin; Haiyan Zhu; Shanlin Chen; Chou Wu; Shaobo Jia; Ghulam Meeladi; Yawei Li; Yixuan Huang (Fuel, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

HILPDA, Regulated by WTAP in an m6A-Dependent Manner, Enhances Osteosarcoma Development by Inhibiting Ferroptosis and Promoting Glycolysis - Yong Jing; Guoyong Zhang; Chenghui Sun; Yawei Pan; Jun Tuo; Zhi Li; Chengji Jiang; Zejian Qiu; Qin Lou (Biochemical Genetics, 2026)

Oxidative carbothermal reduction for preparation of high-loading nano-zero-valent iron doped biochar for removal of tetracyclines and fluoroquinolones - Ahui Sun; Hongru Jiang; Yawei Xiao; Jihui Li (Journal of Environmental Chemical Engineering, 2026)

Efficient removal of N-nitrosodimethylamine and triclosan by nFe@Fe3O4 nanocomposites: Enhanced generation of active hydrogen atoms - Ying Han; Wanqing Zhao; Xiaoping Zheng; Chuwei Li; Lingyun Tang; Tengfei Zhang; Yawei Xie; Hongyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Scale-dependent divergent response of soil respiration and its variation under grazing and reduced precipitation in a sandy Pinus sylvestris var. mongolica plantation - Zi Li; Xu Han; Hengming Zhang; Jiang Zhao; Xiang Li; Guochuang Zhang; Yawei Wei; Shengjin Qin (Journal of Soils and Sediments, 2026)

Netrin-1 protects against doxorubicin-induced cardiotoxicity by suppressing ferroptosis via the UNC5B-LKB1/CaMKKβ-AMPK-NRF2 axis - Wei Lu; Haibo Wu; Yanqing Wang; Yawei Duan; Peng Gao; Hongxiao Li; Rongpin Du (Molecular and Cellular Biochemistry, 2026)

Enhanced reduction of 3-chloronitrobenzene by sulfidated microscale zero-valent iron: Performance and mechanism in anaerobic and aerobic systems - Ying Han; Chuwei Li; Qingjie Lu; Xinhui Ye; Wanqing Zhao; Yawei Xie; Haijiao Xie; Hongyuan Liu (Process Safety and Environmental Protection, 2026)

Integrating electronic sensory, untargeted metabolomics, and FT-NIR spectroscopy with machine learning for rapid origin discrimination and quality assessment of Chebulae Fructus - Yuhang Li; Wei He; Hanwen Zhang; Yue'e Li; Xiaomeng Li; Guokan Ge; Yawei Huang; De Ji (Food Research International, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Injectable self-healing hydrogel for co-delivery of stem cells and growth factors in intervertebral disc regeneration - Zhiming Tu; Weichu Sun; Tao Yuan; Yuliang Dai; Xiaoya Ding; Yawei Li; Xiaocheng Wang; Bing Wang (Chemical Engineering Journal, 2026)

A chitosan-based composite scaffold as a bioactive strontium-delivery system mediating accelerated bone regeneration - Jiyang Zeng; Wei Li; Yawei Li; Zhiming Tu; Hong Ma; Yuliang Dai; Bing Wang; Hongbing Deng (Carbohydrate Polymers, 2026)

Transcriptome profiling of AP2/ERF family members and functional characterization of CaAP2/ERF99 in pepper defense against Phytophthora capsici - Jie Wang; Muhammad Azeem; Yawei Li; Beibei Gong; Xueqi Li; Li Liu; Guangqiang Wu; Moli Chu; Wei Cheng (Plant Science, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Charge-tuning via Al3+-induced between vanadium-oxide layers for robust aqueous zinc-ion batteries - Keli Duan; Ahui Sun; Yawei Xiao; Hongru Jiang; Zhonghua Bao; Xiufen Ma; Jihui Li (Chemical Engineering Journal, 2026)

Human thermal responses to non-uniform cooling from intermittently operated split air conditioners - Haiyan Yan; Yawei Li; Thomas Parkinson; Stefano Schiavon; Hui Zhang; Ruiji Sun; Shengkai Zhao; Wei Zhao; Zhen sun; Fangning Shi (Building and Environment, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Cover crops potentially enhance soil organic carbon sequestration to offset greenhouse gas emissions without yield penalty towards net-zero rice agriculture - Ruitao Lou; Yong Li; Zhenghan Li; Zhifeng Xu; Yu Tang; Xiangping Jin; Junzeng Xu; Yawei Li; Yong He; Qianjing Jiang (Agriculture, Ecosystems & Environment, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Dual-pathway persulfate activation by mackinawite (FeS) for contaminant degradation: Overlooked role of Fe(IV) species and QSAR model - Bowen Yang; Zhihao Li; Yawei Liu; Qiang Ma; Dunqiu Wang; Longhui Zheng; Jiming Hao (Journal of Environmental Management, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Short-term effect of changing water regimes on the soil nematode community in rice-duckweed system under water-saving irrigation - Zeeshan Ahmed; Junzeng Xu; Weixuan Liu; Xiaoyin Liu; Yawei Li; Hang Guo; Shengyu Chen (European Journal of Soil Biology, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

An ensemble method for integrating rainfall forecast products based on average mutual information decomposition - Wei Ding; Minglei Ren; Yawei Ning; Xuan Li; Jinnan Zhang; Huicheng Zhou (Environmental Modelling & Software, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Landslide assessment research in the three gorges reservoir area: A review of methodological advances and future directions - Yuandong Huang; Chong Xu; Xiaoyi Shao; Xiangli He; Zikang Xiao; Xiwei Xu; Yawei Xie; Xuning Nie; Xin Li (Bulletin of Engineering Geology and the Environment, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Phase-resolved multi-path drivers of PM2.5 evolution in eastern China under Clean Air Actions and carbon neutrality scenarios - Yasong Li; Lili Shen; Dandan Wei; Tijian Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie; Yanjin Wang (Journal of Hazardous Materials, 2026)

Anthropogenic filtering of detrital zircon and rutile signals in the Yangtze River: Implications for provenance reconstruction - Rujun Guo; Xianyan Wang; Xilin Sun; Wencke Wegner; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Urs Klötzli; Chang'an Li (Global and Planetary Change, 2026)

Critical nanoparticle formation in iron combustion: single particle experiments with in-situ multi-parameter diagnostics aided by multi-scale simulations - Tao Li; Bich-Diep Nguyen; Yawei Gao; Leon Elsässer; Daoguan Ning; Arne Scholtissek; Adri C.T. van Duin; Christian Hasse; Benjamin Böhm (Fuel, 2026)

Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.

Occurrences and migration characteristics of photoinitiators in paper food packaging: Implication for human exposure - Chenge Qian; Lu Bai; Wen Wang; Yadan Luo; Juan Li; Yawei Wang (Journal of Environmental Sciences, 2025)

Lactobacillus rhamnosus GG-derived extracellular vesicles improve cholestatic liver injury by regulating the gut microbiota and bile acid metabolism - Zhongyu Wang; Yubo Wang; Yawei Qiu; Andrea Del Pilar Abreo Medina; Yongwang Liu; Mengdie Shi; Jinyan Li; Yanyan Wang; Xianjiao Liu; Xingxiang Chen; Kehe Huang; Yunhuan Liu (Chemical Engineering Journal, 2025)

Reversibility of the reproductive toxicity induced by hexafluoropropylene oxide trimer acid (HFPO-TA) in adult zebrafish (Danio rerio) - Dan Yang; Xuan Ren; Xiaohui Zhao; Shasha Dong; Xiaoying Li; Yawei Shi; Ya Sun; Guanghui Ding (Aquatic Toxicology, 2025)

Microbial-mediated transformation shapes the molecular diversity of landfill leachate under anthropogenic and natural covariation - Qiurui Zhang; Jitao Lv; Shiyang Yu; Tianyu Chen; Yue Sun; Feifei Li; Lu Bai; Xianwei Wang; Xiaosong He; Yong Nie; Nanwen Zhu; Yawei Wang; et al. (Water Research, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Dual-action mechanism of Tamarix polyphenols in inhibiting IQ and MeIQ: Synergistic scavenging of free radicals and trapping of reactive carbonyls - Xiaopu Ren; Bing Xie; Mingyang Li; Shuai Kang; Wei Wang; Qianqian Yu; Yawei Zhang; Lujuan Xing (Food Chemistry, 2025)

A Y-shaped DNA-CRISPR-Cas12a Synergy fluorescent aptasensor for ultrasensitive detection of Aflatoxin B1 - Yawei Huang; Muyue Li; Zhuang Yang; Min Wei; Zhiguang Suo (Food Bioscience, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Enhanced CO2 electrolysis via H2/CH4 assistance in a symmetric solid oxide electrolysis cell with an alloy-perovskite composite electrode - Shuangzhen Li; Feiya He; Jing Yan; Yawei Li; Si-Dian Li; Huili Chen (Chemical Engineering Journal, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

Dual roles of N6-methyladenosine in R-loop regulation of gene transcription and genome stability - Fangle Li; Feifan Zhang; Jie Li; Yu Zhang; Wenxuan Gong; Yawei Zhang; Mengxia Liu; Jie Ren; Dali Han (Science China Life Sciences, 2025)

Unraveling the health contributions of five key bioactives in virgin olive oil: A dose-based comparative review - Yunfei Huang; Wenqing He; Mengyao Zhao; David Julian McClements; Yawei Xu; Lu Li; Wanyi Dong; Xueqin Hu; Chunmei Li (Trends in Food Science & Technology, 2025)

A hybrid approach for optimizing soil greenhouse gas flux predictions: integrating machine learning outputs into hyperparameter-tuned regression trees - Mostafa RASTGOU; Shangkun LIU; Jin WANG; Yawei LI; Junzeng XU; Yong HE; Qianjing JIANG (Pedosphere, 2025)

Preparation of nano zero-valent iron-doped magnetic biochar from different types of iron salts: Comparing their adsorption capability for sulfamethoxazole - Kaili He; Ahui Sun; Zijing Guo; Chonglin Zheng; Yujie Jin; Hongru Jiang; Yawei Xiao; Jihui Li (Journal of Environmental Chemical Engineering, 2025)

Effect of catalysts on the conversion of sulfur, nitrogen, and oxygen during catalytic/additives pyrolysis of oil sludge - Zhiguo Zheng; Zhipu Wang; Sikai Wu; Guangpu Li; Yawei Zhai; Lisong Zhou; Jun Yao (Journal of Environmental Chemical Engineering, 2025)

Preparation of magnesia directly from brine Mg(OH)2 and its performance optimization: The role of ZrSiO4 additive - Chengqing Hu; Yibiao Xu; Yawei Li; Wen Yan (Journal of Environmental Chemical Engineering, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Procedural generation of 3D maize plant architecture from LiDAR data - Mozhgan Hadadi; Mehdi Saraeian; Jackson Godbersen; Talukder Z. Jubery; Yawei Li; Lakshmi Attigala; Aditya Balu; Soumik Sarkar; Patrick S. Schnable; Adarsh Krishnamurthy; Baskar Ganapathysubramanian (Computers and Electronics in Agriculture, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Graphene/epoxy coating with radiation heat dissipation properties for spacecraft thermal management - Ning Li; Yibo Zhang; Yawei Xu; Jing Li (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Deformation prediction modeling for levee structures based on environmental loads using SARIMAX and LSTM - Haiyang Li; Jing Wang; Shuguang Wu; Yawei Wang; Yehemin Gao; Guigen Nie (Advances in Space Research, 2025)

Mediating role of whole epigenome DNA methylation signatures in the association between copper and SGA - Weiwei Wu; Mengru Wang; Shan Li; Bole Zhang; Weixuan Hu; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang (Journal of Trace Elements in Medicine and Biology, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

Persistent O3 pollution over the North China Plain during the advancement of East Asian summer monsoon: Process analysis and interannual difference - Libo Gao; Tijian Wang; Xuejuan Ren; Yawei Qu; Hao Wu; Mengmeng Li; Min Xie (Atmospheric Research, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Gram-scale synthesis of unsupported Pt-rare earth nanosponge for enhanced stability in proton exchange membrane fuel cells - Chenhao Li; Hao Wang; Fangren Qian; Yawei Li; Qinqin Sang; Qingjun Chen; Jialiang Liao; Yihan Zhu; Yanrong Liu; Suojiang Zhang (Chemical Engineering Journal, 2025)

Killing two birds with one stone strategy inspired advanced batteries with superior thermal safety: A comprehensive evaluation - Junling Wang; Konghao Yu; Peng Xiao; Li Li; Chunlin Wang; Zhirong Wang; Dongliang Guo; Yuen Kwok Kit Richard; Yawei Lu (Chemical Engineering Journal, 2025)

Water erosion control through vegetation restoration: Mechanisms and contributions of vegetation components in Robinia Pseudoacacia forests - Yang Li; Yawei Hu; Jiongchang Zhao; Jianjun Zhang (CATENA, 2025)

Sustainable Ca(OH)2 deacidifiers derived from waste eggshells for free fatty acids removal: characterization, performance and thermodynamics - Yawei Wang; Chao He; Gang Li; Xinxin Liu; Liang Liu; Youzhou Jiao (Environment, Development and Sustainability, 2025)

Anti-inflammatory effect of food bioactives in inflammatory bowel disease: Role of the gut microbiome - Yawei Zhang; Lufan Zhang; Yang Dong; Yunwei Yang; Mengxing Li; Qian Chen; Dan Wang; Yuzheng Wu; Tao Wang (Food Bioscience, 2025)

Optimizing straw strip-mulching to enhance winter wheat productivity in semi-arid drylands - Rui Li; Yuzhang Chen; Yuwei Chai; Yawei Li; Jiantao Ma; Hongbo Cheng; Lei Chang; Shouxi Chai (Field Crops Research, 2025)

Soil pH modulates the impact of ammonia-based fertilizers on N-cycling microbial genes in terrestrial ecosystems - Xue Zhou; Yiyun Chen; Yawei Li (European Journal of Soil Biology, 2025)

Synergy of bismuth and tungsten in Bi2WO6 for PMS activation to enhance degradation of ammonium dibutyl dithiophosphate in flotation wastewater - Mingwei Shen; Teng Wang; Yawei Wang; Zhiyuan Li; Jiayou Liu; Ke Jin; Hesheng Yu (Journal of Water Process Engineering, 2025)

Influence of alternate wetting and drying and duckweed on zooplankton abundance in rice paddy ecosystem - Zeeshan Ahmed; Weixuan Liu; Junzeng Xu; Yawei Li; Zahid Majeed (Journal of Environmental Management, 2025)

Impact of aerosol-radiation interaction and heterogeneous chemistry on the winter decreasing PM2.5 and increasing O3 in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Journal of Environmental Sciences, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Sucrose laurate and nisin synergistically inhibit Bacillus subtilis by multiple antibacterial targets and play promising application potential in bread preservation - Danya Tong; Panpan Han; Mingrui Li; Zhixin Wang; Zhen Zhao; Yingmin Jia; Yawei Ning (Food Chemistry, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Nuclear receptor 4A1 inhibits chondrocyte inflammation and cartilage degeneration in osteoarthritis by inhibiting NF-κB signal pathway - Yawei Zhang; Hengheng Zheng; Baitong Li (Inflammopharmacology, 2025)

Eco-friendly design of active montmorillonite nanofillers for reinforcing the anti-corrosion property of epoxy coating - Xianliang Li; Yawei Shao; Yanqiu Wang; Junyi Wang (Applied Clay Science, 2025)

Research on multi-objective control algorithm for micro-nano satellite formation based on array signal detection - Jiao Wang; Boao Zhu; Chengshang Li; Chong Sun; Yawei Wan (Advances in Space Research, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Accurate prediction of pollution and health risks of iodinated X-ray contrast media in Taihu Lake with machine learning and revealing key environmental factors - Xinying Cheng; Yuteng Zhang; Sirui Yan; Qingsong Ji; Xiangcheng Kong; Huiming Li; Shiyin Li; Shaogui Yang; Zhigang Li; Yawei Wang; Limin Zhang; Huan He (Water Research, 2025)

Theoretical calculation on degradation mechanism of novel copolyesters under CALB enzyme - Yuanyang Ren; Zhiwen Cheng; Luwei Cheng; Yawei Liu; Mingyue Li; Tao Yuan; Zhemin Shen (Journal of Environmental Sciences, 2025)

Wood-derived closed pore hard carbon encapsulated micro-sized silicon anode design for long-term practical lithium-ion battery - Yingzhe Gao; Kai Zhang; Xiaohang Du; Guihua Liu; Yawei Du; Jingde Li (Chemical Engineering Journal, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Impact of surface reservoir construction on groundwater circulation and recharge in the Yangzhuang karst groundwater system, China - Yawei Feng; Fengxin Kang; Bintao Liu; Lichuan Zhang; Zhifeng Li; Xuetao Xing; Qingcheng He (Hydrogeology Journal, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Recent advances in groundwater pollution research using machine learning from 2000 to 2023: A bibliometric analysis - Xuan Li; Guohua Liang; Bin He; Yawei Ning; Yuesuo Yang; Lei Wang; Guoli Wang (Environmental Research, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

A hybrid TCN-BiLSTM short-term load forecasting model for ship electric propulsion systems combined with multi-step feature processing - Shuo Pang; Liang Zou; Li Zhang; Hui Wang; Yawei Wang; Xingdou Liu; Jundao Jiang (Ocean Engineering, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

Insight into the keystones of Chinese broad bean paste fermentation: Brewing techniques, chemosensory characteristics, and microbial community - Shuai Zhao; Chang Hao; Chengtuo Niu; Jing Lu; Lei Wang; Yawei Shi; Qi Li (Trends in Food Science & Technology, 2024)

Duckweed (Lemna minor L.) as a natural-based solution completely offsets the increase in ammonia volatilization induced by soil drying and wetting cycles in irrigated paddies - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Yixuan Jia; Jian Gao; Qianjing Jiang; Yong He (Science of The Total Environment, 2024)

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

Evolution of hydrochemistry and water quality of karst groundwater under the effects of intense anthropogenic activities - Yawei Feng; Fengxin Kang; Yongli Guo; Zhifeng Li; Bintao Liu; Hongzhi Bu; Chunying Xia; Qingcheng He (Journal of Environmental Management, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

CRISPR-Cpf1 system and its applications in animal genome editing - Yawei Han; Zisen Jia; Keli Xu; Yangyang Li; Suxiang Lu; Lihong Guan (Molecular Genetics and Genomics, 2024)

Discovery of the Miocene Yuanmou Conglomerate and Its Significance for the Drainage Evolution in the Southeastern Tibetan Plateau - Dai Zhang; Chang’an Li; Shitao Zhang; Honglin Yuan; Zengjie Zhang; Yawei Li (Journal of Earth Science, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

The effect of anthropogenic activities on the behavior of novel brominated flame retardants in surface soil of Northern China urbanized zone - Ziyan Liu; Yaqi Zhang; Feifei Li; Huifang Zhong; Runzeng Liu; Qiu Zhang; Rongguang Shi; Yingjun Wang; Yawei Wang (Science of The Total Environment, 2024)

Meta-analysis of GHG emissions stimulated by crop residue return in paddy fields: Strategies for mitigation - Qianying Wu; Ruitao Lou; Yong He; Yawei Li; Zhiming Qi; Junzeng Xu; Ji Liu; Mostafa Rastgou; Qianjing Jiang (Journal of Environmental Management, 2024)

Characteristics of disinfection byproducts from dissolved organic matter during chlor(am)ination of source water in Tibetan Plateau, China - Ruiqing Chen; Tianyu Chen; Yukun Zhou; Linfeng Li; Lingxiangyu Li; Nali Zhu; Zhigang Li; Yawei Wang; Guibin Jiang (Science of The Total Environment, 2024)

Deciphering the seasonal dynamics of multifaceted aerosol-ozone interplay: Implications for air quality management in Eastern China - Yasong Li; Tijian Wang; Qin'geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Jiachen Fan; Min Shao; Min Xie (Science of The Total Environment, 2024)

Synergistic effect of Bi and Fe for suppressing hydrogen evolution reaction (HER) and enhancing electrochemical nitrogen reduction reaction (eNRR) performance - Wenhua Guo; Yawei Li; Si-dian Li; Zongping Shao; Huili Chen (Chemical Engineering Journal, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

The joint impact of PM2.5, O3, and CO2 on the East Asian Summer Monsoon in 2013 and 2018 due to contrasting emission reduction - Danyang Ma; Tijian Wang; Hao Wu; Yawei Qu; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Natalya Andreeva Kilifarska-Nedialkova (Atmospheric Environment, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Antifungal mechanism of Lactiplantibacillus plantarum P10 against Aspergillus niger and its in-situ biopreservative application in Chinese steamed bread - Mengge Ma; Ao Li; Jin Feng; Zhixin Wang; Yingmin Jia; Xinying Ma; Yawei Ning (Food Chemistry, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

High throughput identification of carbonyl compounds in natural organic matter by directional derivatization combined with ultra-high resolution mass spectrometry - Shiyang Yu; Shanshan Tang; Jitao Lv; Feifei Li; Zichun Huang; Lixia Zhao; Dong Cao; Yawei Wang (Water Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Rutile and zircon U-Pb dating as a constraint on sedimentary provenance of the Jianchuan Basin: Implications for paleo-drainage evolution - Rujun Guo; Xilin Sun; Chang'an Li; David Chew; Foteini Drakou; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Jiranan Homnan; Urs Klotzli (Geomorphology, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Assessment major NOx sources to nitrate of TSP around the Danjiangkou reservoir using isotopes and a Bayesian isotope mixing model - Chunyan Xiao; Yimeng Sun; Tongqian Zhao; Guizhen Wang; Pengbo Li; Yawei Zhao; Feihong Chen (Atmospheric Pollution Research, 2024)

A real-time accuracy prediction model on time-relative positioning method considering the correlation of position increment errors - Xuan Zou; Zhiyuan Li; Weiming Tang; Yawei Wang; Yangyang Li; Siyu Zhang; Yongfeng Zhang (GPS Solutions, 2024)

Experimental investigation for the effect of bust pressure on hydrogen explosion venting - Yawei Lu; Rujia Fan; Zhirong Wang; Xingyan Cao; Yongjun Li; Chendi Lin; Zhuohua Yang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Exploring the role of aerosol-ozone interactions on O3 surge and PM2.5 decline during the clean air action period in Eastern China 2014–2020 - Yasong Li; Tijian Wang; Qin'’geng Wang; Mengmeng Li; Yawei Qu; Hao Wu; Min Xie (Atmospheric Research, 2024)

Hydrothermal liquefaction of pig carcasses to biofuel: A techno-economic analysis - Youzhou Jiao; Chao Chang; Gaojie Xu; Chao He; Xinxin Liu; Gang Li; Yawei Wang; Xiaohui Pan; Guizhuan Xu; Qibin Li; Liang Liu (Process Safety and Environmental Protection, 2024)

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Reducing oil absorption in pea starch through two-step annealing with varying temperatures - Shumin Xie; Zihan Li; Qingfei Duan; Weijuan Huang; Wei Huang; Yawei Deng; Pei Chen; Fengwei Xie (Food Hydrocolloids, 2024)

Pollution levels and probability risk assessment of potential toxic elements in soil of Pb–Zn smelting areas - Mingyue Li; Jinyang Zhou; Zhiwen Cheng; Yuanyang Ren; Yawei Liu; Linling Wang; Liu Cao; Zhemin Shen (Environmental Geochemistry and Health, 2024)

Enhanced fluid mixing using a novel multi-stage static pipeline mixer: Numerical simulation and mechanism analysis - Jiaheng Zhao; Xing Li; Zedong Lu; Wenjun Chi; Zhibin Wang; Yawei Chen (Journal of Water Process Engineering, 2024)

Biological effects of perfluoroalkyl substances on running water ecosystems: A case study in Beiluo River, China - Xi Li; Qiang Wang; Qi Li; Yawei Wang; Yulu Tian; Anen He; Yan Chen; Shaocheng Si (Journal of Hazardous Materials, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Proteome and gut microbiota analysis of Chinese mitten crab (Eriocheir sinensis) in response to Hepatospora eriocheir infection - Yawei Cao; Leiting Zhang; Yue Yang; Jiaying Li; Xiaoqi Luan; Xiaoli Xia; Wei Gu; Jie Du; Keran Bi; Li Wang; Qingguo Meng (Aquaculture, 2024)

Hollow core-shell B-g-C3N4-x@Bi2S3/In2S3 dual S-scheme heterojunction photothermal nanoreactor: Boosting photothermal catalytic activity in confined space - Yawei Xiao; Haoyu Li; Bao Yao; Yude Wang (Chemical Engineering Journal, 2024)

Straw strip mulch improves soil moisture similar to plastic film mulch but with a higher net income - Jiantao Ma; Lei Chang; Yawei Li; Xuemei Lan; Wenning Ji; Jiantong Zhang; Fanxiang Han; Hongbo Cheng; Yuwei Chai; Shouxi Chai (Agriculture, Ecosystems & Environment, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

Migration mechanism and risk assessment of per- and polyfluoroalkyl substances in the Ya'Er Lake oxidation pond area, China - Chang Li; Huifang Zhong; Jing Wu; Lingyi Meng; Yingjun Wang; Chunyang Liao; Yawei Wang; Yujian He (Journal of Environmental Sciences, 2024)

Comparative transcriptome analysis and genetic dissection of vegetative branching traits in foxtail millet (Setaria italica) - Tianpeng Liu; Xueying Liu; Jihong He; Kongjun Dong; Lei Zhang; Yawei Li; Ruiyu Ren; Tianyu Yang (Theoretical and Applied Genetics, 2024)

Maximizing the carbon sink function of paddy systems in China with machine learning - Jin Wang; Qingguan Wu; Yong He; Yawei Li; Junzeng Xu; Qianjing Jiang (Science of The Total Environment, 2024)

Research on the direction perception of cruising copepods by the fish lateral line using pressure difference matrix and residual neural network regression method - Yawei Zhu; Yiyuan Gao; Zhaohang Ding; Changran Li; Hao Ding; Yonggang Guo; Dean Hu (Ocean Engineering, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

A technical evaluation on the mathematical attitudes and fitting accuracy of soil moisture retention curve models - Mostafa Rastgou; Yong He; Jin Wang; Hossein Bayat; Meihong Shao; Yawei Li; Qianjing Jiang (Computers and Electronics in Agriculture, 2023)

WITHDRAWN: Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Numerical validation of analytical solutions for tunnels and their applicability evaluation index - Yawei Duan; Jingqi Huang; Mi Zhao; Xu Zhao; Huifang Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

3D reconstruction of plants using probabilistic voxel carving - Jiale Feng; Mojdeh Saadati; Talukder Jubery; Anushrut Jignasu; Aditya Balu; Yawei Li; Lakshmi Attigala; Patrick S. Schnable; Soumik Sarkar; Baskar Ganapathysubramanian; Adarsh Krishnamurthy (Computers and Electronics in Agriculture, 2023)

Quantitative generation of ROS and their effective photocatalytic antibacterial activity of high-intensity universal P25 network films: The role of ROS - Jin Xu; Chengzhuo Yu; Silong Wang; Li Xiong; Fanglan Geng; Jitao Lv; Lixia Zhao; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Analytical solutions for stresses and displacements of tunnels under static and seismic loading - Yawei Duan; Jingqi Huang; Xu Zhao; Mi Zhao; Huifang Li; Xiuli Du (Computers and Geotechnics, 2023)

Charge-tuning mediated rapid kinetics of zinc ions in aqueous Zn-ion battery - Yawei Xiao; Jie Ren; Mengyao Li; Kai Xiao; Yude Wang (Chemical Engineering Journal, 2023)

Ni-rich cathode materials with enhanced kinetics and hydrophobicity endowed by reactive silane coating - Chi Zhang; Tao Li; Xiangkun Wu; Wei Li; Yawei Guo; Suojiang Zhang; Lan Zhang (Chemical Engineering Journal, 2023)

Study on the assimilation of the sulphate reaction rates based on WRF-Chem/DART - Congwu Huang; Chaoqun Ma; Tijian Wang; Yawei Qu; Mengmeng Li; Shu Li; Bingliang Zhuang; Min Xie (Science China Earth Sciences, 2023)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Identification of lower brominated bisphenol A analogs as the photooxidation products of tetrabromobisphenol A bis(2,3-dibromopropyl) ether (TBBPA-BDBPE) - Yuqing Jiang; Ling Wang; Minggang Zheng; Yongfeng Lin; Aifeng Liu; Yawei Wang; Ying Li (Science of The Total Environment, 2023)

Absence of known knockdown resistance mutations but fixation of CYP337B3 was detected in field populations of Helicoverpa armigera across China - Ruoyao Ni; Yawei Wang; Qiuzan Zhong; Mei Li; Dandan Zhang; Yongjun Zhang; Xinghui Qiu (Pesticide Biochemistry and Physiology, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Identification of natural and anthropogenic sources and the effects of climatic fluctuations and land use changes on dust emissions variations in the Qinghai-Tibetan Plateau - Heqiang Du; Yawei Fan; Lihui Luo; Jie Liao; Zongxing Li; Xiufan Liu; Xinlei Liu; Xian Xue; Tao Wang (Agricultural and Forest Meteorology, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Protective effect of chicken egg yolk immunoglobulin (IgY) against Spiroplasma eriocheiris infection in Chinese mitten crab - Ying Guo; Yubo Ma; Hendriansyah Endri; Yanlan Huang; Xinyu Pan; Suyue Qiu; Yawei Cao; Wei Gu; Jie Du; Li Wang; Qingguo Meng (Aquaculture, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Developmental Toxicity and Cardiotoxicity Induced by PFOS and its Novel Alternative OBS in Early Life Stage of Zebrafish (Danio rerio) - Dan Yang; Xiaohui Li; Shasha Dong; Xiaohui Zhao; Xiaoying Li; Meng Zhang; Yawei Shi; Guanghui Ding (Water, Air, & Soil Pollution, 2023)

Reaction mechanism of NO and SO2 Co-removal by calcium hydroxide - Angran Zhao; Yongqiang Han; Zhipeng Wang; Pengfei Li; Yawei Xu; Ruiming Yang; Huiling Tong (Journal of Environmental Chemical Engineering, 2023)

Distribution characteristics of photoinitiators and their flux estimation from the Pearl River Delta to the coastal waters of the South China Sea - Yuqing He; Zibin Pan; Xinxin Liang; Ruiman Xie; Yuying Sun; Juan Li; Yawei Wang; Lixi Zeng (Journal of Environmental Sciences, 2023)

Efficient anti-frosting on discrete nanoclusters via spatiotemporal control of condensation frosting dynamics - Siyan Yang; Yushan Ying; Wanbo Li; Yawei Feng; Rongfu Wen; Qixun Li; Yuanbo Liu; Bingang Du; Zuankai Wang; Xuehu Ma (Chemical Engineering Journal, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Pretreatment of moso bamboo with p-toluenesulfonic acid for the recovery and depolymerization of hemicellulose - Meixin Wang; Yawei Zhan; Jiayue Zhao; Zhiqiang Li (Bioresource Technology, 2023)

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Distribution and exposure risk assessment of chlorinated paraffins and novel brominated flame retardants in toys - Ruirui Zhang; Juan Li; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Analytical solution for the temperature field of an elliptical tunnel in cold regions - Yanhu Zhao; Jing Zhang; Linjing Li; Taotao Hu; Yawei Zhao (Cold Regions Science and Technology, 2023)

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Evaluating the dynamic distribution process and potential exposure risk of chlorinated paraffins in indoor environments of Beijing, China - Lu Bai; Kun Lv; Juan Li; Wei Gao; Chunyang Liao; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Synergistic modification of Ni-rich full concentration gradient materials with enhanced thermal stability - Chi Zhang; Tao Li; Bing Xue; Xiangkun Wu; Liyuan Li; Yawei Guo; Lan Zhang (Chemical Engineering Journal, 2023)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Bone Marrow Mesenchymal Stem Cell-Derived Exosomal microRNA-29b-3p Promotes Angiogenesis and Ventricular Remodeling in Rats with Myocardial Infarction by Targeting ADAMTS16 - Jialin Zheng; Xinjin Zhang; Wenfeng Cai; Yawei Yang; Tao Guo; Jianmei Li; Hualei Dai (Cardiovascular Toxicology, 2022)

Research on Surrounding Rock Control Technology of Gob-Side Entry Retaining by Directional Roof Cutting in a Deep Coal Mine - Haojie Xue; Shibao Shen; Haoran Lu; Renbao Zhao; Peishuai Li; Yawei Zhao; Qibin Jiang; Longjiang Wang; Beizhan Fan; Tao Qin (Geotechnical and Geological Engineering, 2022)

Water splitting, pollutant degradation and environmental impact using low-index faceted metal-based nanocrystals. A review - Xiang Zhang; Jie Tang; Nali Zhu; Lingxiangyu Li; Yawei Wang (Environmental Chemistry Letters, 2022)

CRISPR-Cas9-Mediated Gene Therapy in Neurological Disorders - Lihong Guan; Yawei Han; Ciqing Yang; Suxiang Lu; Jiang Du; Han Li; Juntang Lin (Molecular Neurobiology, 2022)

Variations of human cerebral and ocular blood flow during exposure to multi-axial accelerations - Weipeng Li; Bitian Wang; Yawei Wang; Xiaoyu Liu; Wentao Feng; Tianya Liu; Zhujun Sun; Yu Liu; Songyang Liu; Yubo Fan (Medical & Biological Engineering & Computing, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Characterization of plant growth-promoting traits of Enterobacter sp. and its ability to promote cadmium/lead accumulation in Centella asiatica L. - Yi Li; Lijuan Mo; Xiaoqin Zhou; Yawei Yao; Jiangming Ma; Kehui Liu; Fangming Yu (Environmental Science and Pollution Research, 2022)

Changing incidence and projections of thyroid cancer in mainland China, 1983–2032: evidence from Cancer Incidence in Five Continents - Mandi Li; Jiao Pei; Minghan Xu; Ting Shu; Chengjie Qin; Meijing Hu; Yawei Zhang; Min Jiang; Cairong Zhu (Cancer Causes & Control, 2021)

A comparative analysis of navigation signals in BDS-2 and BDS-3 using zero-baseline experiments - Chenlong Deng; Shufeng Qi; Yangyang Li; Yawei Wang; Xuan Zou; Weiming Tang; Chi Guo (GPS Solutions, 2021)

Manganese Accumulation and Plant Physiology Behaviour of Camellia oleifera in Response to Different Levels of Phosphate Fertilization - Fangming Yu; Meifen Xin; Yawei Yao; Xueru Wang; Kehui Liu; Yi Li (Journal of Soil Science and Plant Nutrition, 2021)

Visualization of GNSS multipath effects and its potential application in IGS data processing - Weiming Tang; Yawei Wang; Xuan Zou; Yangyang Li; Chenlong Deng; Jianhui Cui (Journal of Geodesy, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Sorptive removal of methylene blue from water by magnetic multi-walled carbon nanotube composites - Guobin Song; Anqi Li; Yawei Shi; Wanran Li; Haonan Wang; Chunchao Wang; Ruijuan Li; Guanghui Ding (Environmental Science and Pollution Research, 2021)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Enterobacter sp. FM-1 inoculation influenced heavy metal-induced oxidative stress in pakchoi (Brassica campestris L. ssp. Chinensis Makino) and water spinach (Ipomoea aquatic F.) cultivated in cadmium and lead co-contaminated soils - Fangming Yu; Yawei Yao; Jingpei Feng; Xueru Wang; Jiangming Ma; Kehui Liu; Yi Li (Plant and Soil, 2021)

Nitrification inhibitor DMPP offsets the increase in N2O emission induced by soil salinity - Yawei Li; Junzeng Xu; Xiaoyin Liu; Zhiming Qi; Haiyu Wang; Youjia Li; Linxian Liao (Biology and Fertility of Soils, 2020)

Lithology identification and reservoir characteristics of the mixed siliciclastic-carbonate rocks of the lower third member of the Shahejie formation in the south of the Laizhouwan Sag, Bohai Bay Basin, China - Yajun Duan; Jun Xie; Baichuan Li; Mengqi Wang; Tianqi Zhang; Yawei Zhou (Carbonates and Evaporites, 2020)

The Influence of Temperature and High-Speed Heating on Tensile Strength of Granite and the Application of Digital Image Correlation on Tensile Failure Processes - Fei Wang; Heinz Konietzky; Thomas Frühwirt; Yawei Li; Yajie Dai (Rock Mechanics and Rock Engineering, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Income inequality and CO2 emissions in belt and road initiative countries: the role of democracy - Wanhai You; Yehua Li; Peng Guo; Yawei Guo (Environmental Science and Pollution Research, 2020)

5-FU preferably induces apoptosis in BRAF V600E colorectal cancer cells via downregulation of Bcl-xL - Tongfei Shi; Mohan Gao; Meihui He; Fengli Yue; Yawei Zhao; Madi Sun; Kan He; Li Chen (Molecular and Cellular Biochemistry, 2019)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

Ammonia volatilization and nitrogen leaching following top-dressing of urea from water-saving irrigated rice field: impact of two-split surge irrigation - Junzeng Xu; Boyi Liu; Haiyu Wang; Wenhao Liu; Yawei Li; Yubin Dai; Tao Lu (Paddy and Water Environment, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Influence of Atmospheric Particulate Matter on Ozone in Nanjing, China: Observational Study and Mechanistic Analysis - Yawei Qu; Tijian Wang; Yanfeng Cai; Shekou Wang; Pulong Chen; Shu Li; Mengmeng Li; Cheng Yuan; Jing Wang; Shaocai Xu (Advances in Atmospheric Sciences, 2018)

Design of gas drainage modes based on gas emission rate in a gob: a simulation study - Xiaowei Li; Chaojie Wang; Yujia Chen; Jun Tang; Yawei Li (Arabian Journal of Geosciences, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

Instantaneous BDS + GPS undifferenced NRTK positioning with dynamic atmospheric constraints - Xuan Zou; Yawei Wang; Chenlong Deng; Weiming Tang; Zongnan Li; Jianhui Cui; Chen Wang; Chuang Shi (GPS Solutions, 2018)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Fouling analysis of membrane bioreactor treating antibiotic production wastewater at different hydraulic retention times - Dawei Yu; Yutao Chen; Yuansong Wei; Jianxing Wang; Yawei Wang; Kun Li (Environmental Science and Pollution Research, 2017)

Mapping the effect of escitalopram treatment on amplitude of low-frequency fluctuations in patients with depression: a resting-state fMRI study - Li Wang; Xueni Li; Ke Li; Yunai Su; Yawei Zeng; Qinge Zhang; Gang Wang; Zhen Jin; Qingmei Kong; Tianmei Si (Metabolic Brain Disease, 2017)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Hyperthermostable Thermotoga maritima xylanase XYN10B shows high activity at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids - Tianyi Yu; Sasikala Anbarasan; Yawei Wang; Kübra Telli; Aşkın Sevinç Aslan; Zhengding Su; Yin Zhou; Li Zhang; Piia Iivonen; Sami Havukainen; Tero Mentunen; Michael Hummel; et al. (Extremophiles, 2016)

Effects of vegetation and soil texture on surface soil moisture retrieval using multi-temporal optical and thermal infrared observations - Pei Leng; Xiaoning Song; Zhao-Liang Li; Yawei Wang; Di Wang (International Journal of Remote Sensing, 2015)

Air Quality in Lanzhou, a Major Industrial City in China: Characteristics of Air Pollution and Review of Existing Evidence from Air Pollution and Health Studies - Yaqun Zhang; Min Li; Mercedes A. Bravo; Lan Jin; Amruta Nori-Sarma; Yanwen Xu; Donghong Guan; Chengyuan Wang; Mingxia Chen; Xiao Wang; Wei Tao; Weitao Qiu; et al. (Water, Air, & Soil Pollution, 2014)

Polymorphisms in DNA repair genes, hair dye use, and the risk of non-Hodgkin lymphoma - Huan Guo; Bryan A. Bassig; Qing Lan; Yong Zhu; Yawei Zhang; Theodore R. Holford; Brian Leaderer; Peter Boyle; Qin Qin; Cairong Zhu; Ni Li; Nathaniel Rothman; et al. (Cancer Causes & Control, 2014)

Biomass carbon storage and its sequestration potential of afforestation under natural forest protection program in China - Wangming Zhou; Bernard Joseph Lewis; Shengnan Wu; Dapao Yu; Li Zhou; Yawei Wei; Limin Dai (Chinese Geographical Science, 2014)

Forest carbon storage and tree carbon pool dynamics under natural forest protection program in northeastern China - Yawei Wei; Dapao Yu; Bernard Joseph Lewis; Li Zhou; Wangming Zhou; Xiangmin Fang; Wei Zhao; Shengnan Wu; Limin Dai (Chinese Geographical Science, 2014)

Role of one-carbon metabolizing pathway genes and gene–nutrient interaction in the risk of non-Hodgkin lymphoma - Qian Li; Qing Lan; Yawei Zhang; Bryan A. Bassig; Theodore R. Holford; Brian Leaderer; Peter Boyle; Yong Zhu; Qin Qin; Stephen Chanock; Nathaniel Rothman; Tongzhang Zheng (Cancer Causes & Control, 2013)

Multilayer Pressure Containment Model and its Application in Deep Well Fractured Formation - Pei Yang; Mian Chen; Yan Jin; Bing Hou; Yunhu Lu; Chuan Liang; Qianqian Zhu; Yawei Li (Rock Mechanics and Rock Engineering, 2013)

Subtype of dietary fat in relation to risk of Hodgkin lymphoma: a population-based case–control study in Connecticut and Massachusetts - Yongshun Gao; Qian Li; Bryan A. Bassig; Ellen T. Chang; Min Dai; Qin Qin; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

Body size and risk of Hodgkin’s lymphoma by age and gender: a population-based case–control study in Connecticut and Massachusetts - Qian Li; Ellen T. Chang; Bryan A. Bassig; Min Dai; Qin Qin; Yongshun Gao; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Light at night and breast cancer risk: results from a population-based case–control study in Connecticut, USA - Qian Li; Tongzhang Zheng; Theodore R. Holford; Peter Boyle; Yawei Zhang; Min Dai (Cancer Causes & Control, 2010)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)

Genotype frequency and F ST analysis of polymorphisms in immunoregulatory genes in Chinese and Caucasian populations - Qing Lan; Min Shen; Dino Garcia-Rossi; Stephen Chanock; Tongzhang Zheng; Sonja I. Berndt; Vinita Puri; Guilan Li; Xingzhou He; Robert Welch; Shelia H. Zahm; Luoping Zhang; et al. (Immunogenetics, 2007)